The mechanics of the Industrial Revolution - Morgan Kelly; Cormac Ó Gráda; Joel Mokyr (University College Dublin, UCD Centre for Economic Research, 2020)
For contemporaries, Britain's success in developing the technologies of the early Industrial Revolution rested in large part on its abundant supply of artisan skills, notably in metalworking. In this paper we outline a simple process where successful industrialization occurs in regions that start with low wages and high mechanical skills, and show that these two factors strongly explain the growth of the textile industry across the 41 counties of England between the 1760s and 1830s. By contrast, literacy and access to capital have no power in predicting industrialization, nor does proximity to coal. Although unimportant as a source of power for early textile machinery, Britain's coal was vital as a source of cheap heat that allowed it over centuries to develop a unique range of sophisticated metalworking industries. From these activities came artisans, from watchmakers to iron founders, whose industrial skills were in demand not just in Britain but across all of Europe. Against the view that living standards were stagnant during the Industrial Revolution, we find that real wages rose sharply in the industrializing north and collapsed in the previously prosperous south.
Keywords: 330; Handwerksberufe; Metallberufe; Industrialisierung; Wirtschaftsgeschichte; Großbritannien